Effect of Contact Pesticides on Vine Mealybug Parasitoids, Anagyrus sp. near pseudococci (Girault) and Coccidoxenoides perminutus (Timberlake) (Hymenoptera: Encyrtidae) - Mgocheki, N.; Addison, P. (South African Journal of Enology and Viticulture, 2016)
Anagyrus species near pseudococci (Girault) and Coccidoxenoides perminutus (Timberlake) (Hymenoptera: Encyrtidae) are well-known mealybug parasitoids. Both are proven biological control agents of Planococcus ficus (Signoret) (Hemiptera: Pseudococcidae) in vineyards. These parasitoids are affected by some pesticides used for the control of ants (Hymenoptera: Formicidae) and P. ficus in vineyards. To establish which of the vineyard pesticides is more toxic to parasitoids, pesticide bioassays were carried in the laboratory using adult and pupal parasitoids. Fipronil and α-cypermethrin caused significant acute toxicity of both parasitoids. Low mortality was recorded for all these pesticides for parasitoids emerging from mummies indicating that the mummy case was an effective barrier to pesticides for parasitoids. Buprofezin, mancozeb and an insecticidal soap were not toxic to parasitoids in both bioassays. Some pesticides have far-reaching negative impacts on parasitoids of orchard and vineyard arthropod pests. A refinement on pest management strategies regarding method and timing of application of pesticides where parasitoids constitute part of the pest management program is essential.